PERLINDUNGAN HUKUM BAGI ANAK LUAR KAWIN ATAS HARTA WARISAN BAPAK BIOLOGIS KARENA PERKAWINAN ORANG TUANYA YANG BELUM DICATATKAN - Indira Erlyanti; Lanny Kusumawati; Sriwati Sriwati (Perpustakaan Universitas Surabaya, 2018)
In law there are events or events in human life that need to be registered officially so that there is certainty about the incident such as marriage, birth, confession of birth, divorce, and death. Marriage is the inner bond between a man and a woman as husband and wife, whereas the purpose of marriage is to form a happy, everlasting family / household based on the One Godhead. Marriage is the same as important events in the life of a person, so it needs to be listed to give legitimacy to both parties both husband and wife. In addition to forming a happy family / household, marriage also has another purpose to get offspring or children. The status of the child has been known to be a legitimate child, an outsider and an adopted child. Subjects concerning the status of children outside marriage or children born to unmarried fathers and mothers in a marriage are called illegitimate children or married children having a civil relationship with their mother and mother's family, as mentioned in Article 43 paragraph (1) of Law no. 1 Year 1974 About Marriage. Inheritance is a law that regulates the transfer of ownership rights to the heirs to the heirs, determines who has the right to become an heir and what part thereof. This means that inheritance occurs due to the death of Article 830 of the Civil Code, which determines that inheritance only occurs due to death.